Penerapan Model Quantum Teaching untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SDN 147 Pekanbaru - Susanti, Novi; Alim, Jesi Alexander; Lazim, Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThe purpose of this research is to increase the result of learning mathematics on IV grade student of SDN 147 Pekanbaru through application model Quantum Teaching. The main question in this research is can application of model Quantum Teaching improve the result of studying mathematics of IV grade SDN 147 Pekanbaru students??. Hypothesis of this research is : if applying model Quantum Teaching can increase learning outcome. This research consist of three cycles. Percentage of teacher?s activities in cycle I was 68,75% (good chategory), in cycle II was 81,25% (good chategory), in cycle III was 93,75% (very good chategory). Percentage of student?s activities in cycle I was 60,41% (good chategory), in cycle II was 79,16% (good chategory), in cycle III was 93,75% (very good chategory). Based on analysis data and discussion of the research the mean score of student?s learning outcome was increased. The mean of student?s outcome from 62,83 point in cycle I was 68,78 point, in cycle II increased to 76,37 point, in cycle III increased to 83,86 point. From that data is can be coucluded that the application of model Quantum Teaching can increase the result of studying mathematics of IV grade students in SD Negeri 147 Pekanbaru.Key Words: Model, Quantum Teaching, Mathematics achievement